The Implementation of Psychoeducational Group with Role Play and Symbolic Modelling Techniques to Improve the Interpersonal Communication of the Guidance and Counseling Students of Universitas IKIP Veteran Semarang - Kurniawan, Tomi; Sugiyo, Sugiyo; Purwanto, Edy (Jurnal Bimbingan Konseling)
This study aimed at examining and analyzing the implementation of psychoeducational group with role play to improve the interpersonal communication of guidance and counseling students. This study used pretest-posttest comparison group design. Meanwhile, purposive sampling was used to select 18 experimental subjects placed in two groups randomly so that each group consisted of nine students. Their data were collected using interpersonal communication scale. The results of wilcoxon test showed that the implementation of psychoeducational group with role play and symbolic modelling and the combination of both techniques was effective to improve students? interpersonal communication. Further, the implication of the study findings are discussed in the discussion chapter.